Membrane potential - Sevigny, Charles (Henry Stewart Talks, 2022)
Physiology, Membrane potential, Excitable cells, Equilibrium potential, Resting membrane potential, Sodium permeability, Potassium permeability, Action potential generation, Sodium-Potassium pump, Nernst potential